Biochip Development for Biological Cells Manipulation Using DEP - Siti Nursyahirah, Ahmad Latfi; Fahmi, Samsuri (Asian Research Publishing Network (ARPN), 2015)
Biochip is a technology platform that has become the medium of researchers in carrying out the analysis of biological cells such as sorting, trapping and screening of biological within a few seconds. To conduct analysis on biological cells, appropriate manipulation techniques are required. In this research, a Dielectrophoresis force (DEP) manipulation technique was used by applying non-uniform AC electric fields generated by the microeletrodes designed. For carrying out on one of the main objectives of this study, COMSOL Multiphysics 4.4 software was used in this study in which the ring planar microarray microelectrodes pattern was designed to investigate the distribution of the electric field resulting from the microelectrodes designed. Results show the highest electric field strength occurs at the end of the microelectrode tip at the same time the lowest electric field region can be seen at the microcavity centre. Cell trapping may also occur in the central part of the micro-cavities with negative dielectrophoresis (nDEP) in which cells will become interested in the low electric field.